Pengaruh Career Development Dan Non-Physical Work Environment Terhadap Employee Retention Dimediasi Job Satisfaction Pada Karyawan RS Mary Cileungsi Kab.Bogor - Hidayat, Cecep Enday; Setyaningrum, Retno Purwani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Abstracts Employee retention is one of the company's ability activities to retain employees who have the potential to remain loyal to the company in the long term. The aim of employee retention is to retain employees who are considered to have quality as long as possible, because employees who have the best quality are one of the supporting factors in advancing the organization in the future company. The aim of this research is to determine the effect of career development and non-physical work environment on employee retention with job satisfaction as an intervening variable. This research used quantitative methods with a sample of 105 employees at Mary Cileungsi Hospital. This research was processed using SmartPLS data processing software and data collection was carried out via Google forms. This research shows that career development has a significant influence on employee retention, the non-physical work environment has a positive and significant influence on employee retention, and there is no influence between job satisfaction and employee retention, there is a significant influence between career development on job satisfaction, the non-physical work environment has an influence positive and significant on job satisfaction, career development has a significant effect on employee retention mediating job satisfaction and job satisfaction can mediate the non-physical work environment on employee retention.